Morphological and Molecular Characterization of Major Quince Cultivars from Turkey - Hasan PINAR; Suat KAYMAK; Serif OZONGUN; Aydın UZUN; Mustafa UNLU; Mustafa BIRCAN; Sezai ERCISLI; Emine ORHAN (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 2016)
Quince (Cydonia oblonga Mill.) belongs to the Rosaceae family is native to south-eastern Europa and Asia Minor. It is generally used for table consumption and processed into jam, jelly and marmalade. It is also used as dwarfing rootstock for pear cultivars. In the present study, fruit characteristics and genetic diversity of 17 quince cultivars from Turkey were investigated. For fruit characteristics, ‘Bardacik’ had the highest fruit weight. The highest SSC/Acidity ratio were obtained from ‘Osmancik’. There was high level of variation in fruit characteristics among cultivars. In molecular analysis, totally 133 bands were obtained from 23 sequence-related amplified polymorphism (SRAP) primer combinations and 67 of them were polymorphic. Genetic similarity of 17 cultivars was between 0.78 and 1.00. Two cultivars (‘Sekergevrek’ and ‘32S04’) were found to be more distinct from the other cultivars genetically. This study showed that there was low level of genetic variation most of quince cultivars grown in Turkey. SRAP markers firstly used in quince with this study indicating that it can be used for characterization and diversity analysis of quince.